1998
DOI: 10.3171/foc.1998.5.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone or tirilazad mesylate administration after acute spinal cord injury: 1-year follow up

Abstract: Object A randomized double-blind clinical trial was conducted to compare neurological and functional recovery and morbidity and mortality rates 1 year after acute spinal cord injury in patients who had received a standard 24-hour methylprednisolone regimen (24MP) with those in whom an identical MP regimen had been delivered for 48 hours (48MP) or those who had received a 48-hour tirilazad mesylate (48TM) regimen. Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
121
0
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 25 publications
0
121
0
6
Order By: Relevance
“…Three large, double-blind, placebocontrolled pharmaceutical trials focussed on acute neuroprotection and rehabilitation in SCI are reported in the literature; the National Acute Spinal Cord Injury Study (NASCIS), Sygen and GK-11 trials. [2][3][4][5][6][7][8] The data from the placebo-control groups in these studies allow the natural history of recovery from injury to be examined within the context of a randomized controlled trial (RCT). In addition, there have been a number of studies of long-term outcomes after SCI that provide valuable information on expected recovery rates, [10][11][12] as well as some recently unpublished data from the European Multicenter study in Spinal Cord Injury (EMSCI).…”
Section: Sources Of Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Three large, double-blind, placebocontrolled pharmaceutical trials focussed on acute neuroprotection and rehabilitation in SCI are reported in the literature; the National Acute Spinal Cord Injury Study (NASCIS), Sygen and GK-11 trials. [2][3][4][5][6][7][8] The data from the placebo-control groups in these studies allow the natural history of recovery from injury to be examined within the context of a randomized controlled trial (RCT). In addition, there have been a number of studies of long-term outcomes after SCI that provide valuable information on expected recovery rates, [10][11][12] as well as some recently unpublished data from the European Multicenter study in Spinal Cord Injury (EMSCI).…”
Section: Sources Of Datamentioning
confidence: 99%
“…Patients were examined on admission to hospital emergency room, mostly within 12 h after injury, and an average time from injury to treatment of 8.9 h. In this second study, 2,3 487 patients were enrolled, of whom 171 were in the placebo group, and outcomes measured at 6 weeks, 6 months and 1 year. The third NASCIS study 4,5 did not have a placebo-control group, because following its apparent efficacy in the NASCIS II study it was considered that to deny some form of methylprednisolone treatment would be unethical. 2.…”
Section: Sources Of Datamentioning
confidence: 99%
“…15 As long as there is neither compression of the cord nor fracture or instability of the spine, application of high-dose methylprednisolone currently is the only treatment option in case of post-traumatic cord oedema, even though the success of steroid therapy for this indication remains moderate. 7,26 Neurocompression is an indication for operation; however, overt instability of the cervical spine because of discoligamentous injury alone also requires surgery in order to prevent continued damage to the cord. 12 In such conditions, we prefer an anterolateral approach with decompression of the thecal sac by removal of the disrupted disc and the rolled-up parts of the posterior ligament.…”
Section: Discussionmentioning
confidence: 99%
“…The two most widely discussed are the National Acute Spinal Cord Injury Study (NASCIS) trial of high-dose systemic methylprednisolone (MP) 3 and the Sygen s trial of GM-1 gangliosides. 4 GM-1 gangliosides appeared to enhance the rate of recovery from SCI, but did not significantly improve the ultimate functional outcome, whereas MP was reported to improve functional outcome when administered within 8 h of SCI.…”
Section: Neuroprotection In the Setting Of Scimentioning
confidence: 99%